2017
DOI: 10.1177/0018726717706535
|View full text |Cite
|
Sign up to set email alerts
|

Occupational limbo, transitional liminality and permanent liminality: New conceptual distinctions

Abstract: This article contributes new theoretical perspectives and empirical findings to the conceptualization of occupational liminality. Here, we posit ‘occupational limbo’ as a state distinct from both transitional and permanent liminality; an important analytic distinction in better understanding occupational experiences. In its anthropological sense, liminality refers to a state of being betwixt and between; it is temporary and transitional. Permanent liminality refers to a state of being neither-this-nor-that, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(115 citation statements)
references
References 61 publications
(143 reference statements)
1
113
0
1
Order By: Relevance
“…From different theoretical perspectives, research on identity in liminal contexts has identified how people take different identity positions to create or maintain identity stability (Hay & Samra‐Fredericks, ; Ibarra & Obodaru, ). We argue that participants’ constructions of continuous selves serve as responses to unstable and sometimes identity‐threatening liminal contexts (Bamber et al ., ). In this way, our findings confirm previous research into liminal identity work and expand our understanding of discursive strategies that people may use to make sense of themselves and their experiences in liminal contexts.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…From different theoretical perspectives, research on identity in liminal contexts has identified how people take different identity positions to create or maintain identity stability (Hay & Samra‐Fredericks, ; Ibarra & Obodaru, ). We argue that participants’ constructions of continuous selves serve as responses to unstable and sometimes identity‐threatening liminal contexts (Bamber et al ., ). In this way, our findings confirm previous research into liminal identity work and expand our understanding of discursive strategies that people may use to make sense of themselves and their experiences in liminal contexts.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies show that people in liminality voice an intense desire for both self and structural stability and ‘fixedness’ (Hay & Samra‐Fredericks, ). Others feel trapped in a transitory state by insurmountable structural barriers (Bamber et al ., ). If some of these barriers can be overcome, identity work can be particularly creative in liminal spaces (Ibarra & Obodaru, ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Finding a way out from such a situation may be difficult if one experiences it as being constantly in a 'fast-moving train' (Johnsen & Sørensen 2015). A frustration caused by the simultaneous impossibility and unavoidability of finding a solution may feel like schitzophrenic aporia (Czarniawska & Mazza 2003) or limbo (Bamber et al 2017). Facing this situation alone increases its difficulty (Johnsen & Sørensen 2015).…”
Section: Literature Liminality As the Condition Of Modernity: From A mentioning
confidence: 99%
“…The social environment has emerged from the direction and behaviours of those who are dominant within the field. Bamber et al (2017) further develop the theorising on the concept of liminality by distinguishing van Gennep's original definition as 'transitional liminality', with two other related concepts: permanent liminality, which "creates an enduring sense of being neither-Xnor-Y or indeed of being both-X-and-Y" (Bamber et al, 2017: 3); and limbo, which is "a fixed, 'trapped' state…not moving towards a threshold" (Bamber et al, 2017: 8). This i t a t i v e R e s e a r c h i n O r g a n i z a t i o n s a n d M a n a g e m e 4 distinction is important, as 'limbo' is frequently but imprecisely used in common parlance.…”
Section: Conceptualizing Liminality Limbo and Identity Statesmentioning
confidence: 99%